2020
DOI: 10.17352/2455-5479.000095
|View full text |Cite
|
Sign up to set email alerts
|

A survey of hand hygiene knowledge, attitude and practices among health care workers in a tertiary hospital, Southwestern Nigeria

Abstract: Background: Improper hand hygiene practices among Healthcare Providers (HCPs) are a common risk factor for and interventions to improve hygiene have proven to be effective strategy in reducing nosocomial infection. Hand hygiene has been described as the single most important, simplest and least expensive means of preventing nosocomial infections. Aim/Objectives: The studied was carried out to determine the knowledge, attitude and practice of hand hygiene among healthcare workers in a tertiary health facility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…As a result, NIs are seen as a major public health risk for patients, healthcare staff, and the health-care system. 18 In this study we found that hand hygiene practice, either hand washing or hand rubbing can decrease the incidence of NI or other related parameters, although hand rubbing is seeems more superior than hand washing. However.…”
Section: Discussionmentioning
confidence: 62%
“…As a result, NIs are seen as a major public health risk for patients, healthcare staff, and the health-care system. 18 In this study we found that hand hygiene practice, either hand washing or hand rubbing can decrease the incidence of NI or other related parameters, although hand rubbing is seeems more superior than hand washing. However.…”
Section: Discussionmentioning
confidence: 62%
“…Assefa et al in Northeast Ethiopia reported that 55% of healthcare providers had safe infection prevention practices 29 . Agbana reported that only 53.4% of participants had received training on hand washing in the last 3 years of experience in Nigeria, 30 while Gasabaet al from Zimbabwe found that 79.3% of participants washed their hands and 75.9% were aware that the infection control manual guideline was available in their workplace 5 . Our findings align with a study conducted in Uganda which reported that nurses' attitudes improved with greater work experience, making them better models for younger employees 31 .…”
Section: Discussionmentioning
confidence: 99%